Is laparoscope surgery feasible for upper gastrointestinal cancer patients with a history of abdominal surgery? - Li, Feng; Zhang, Fan; Liu, Weixin; Zheng, Qingfeng; Zhang, Moyan; Wang, Zhen; Zhang, Xuefeng; Qi, Ling; Li, Yong (Frontiers in Surgery, 2023)
Objective To investigate the feasibility of laparoscopic abdominal mobilization in patients with cancers of the esophagus or gastroesophageal junction who have a history of abdominal surgery. Methods A total of 132 patients who underwent resection for cancers of the esophagus or gastroesophageal junction from August 2018 to March 2022 in the Department of Thoracic Surgery, Cancer Hospital, Chinese Academy of Medical Sciences, were selected (66 patients with a history of abdominal surgery (observation group) and 66 patients without a history of abdominal surgery (control group)). All patients were treated with preoperative neoadjuvant therapy, based on the clinical stage. Thoracoscopic and laparoscopic resection was performed under general anesthesia. The intraoperative and postoperative conditions and surgical complications were compared between the two groups. Results No significant differences were found in baseline data between the observation group and the control group (p>0.05). Laparoscopic abdominal mobilization was completed in both groups, and there were no significant differences between the two groups in the total operation time [(272.50±86.45) min vs. (257.55±67.96) min], abdominal mobilization time [(25.03±9.82) min vs. (22.53±3.88) min], blood loss [(119.09±72.17) mL vs. (104.39±43.82) mL], and postoperative time to first flatus [(3.44±0.73) d vs. (3.29±0.60) d] (p>0.05). The abdominal mobilization time was longer in observation group than that in control group (p=0.057). After excluding the patients (31/66) with a history of simple appendectomy from the observation group, the abdominal mobilization time was significantly longer in observation group than that in control group [(27.97±12.16) min vs. (22.53±3.88) min] (p<0.05). There were significantly fewer dissected abdominal lymph nodes in the observation group than in the control group [(18.44±10.87) vs. (23.09±10.95), p<0.05]. After excluding the patients (15/66) with a history of abdominal tumor surgery from the observation group, there was no significant difference in the number of dissected abdominal lymph nodes between the two groups [(20.62±10.81) vs. (23.09±10.95)] (p>0.05).In addition, no postoperative complications, such as intestinal obstruction, abdominal infection and bleeding, occurred in either group. Conclusion Patients with cancers of the esophagus or gastroesophageal junction who have a history of abdominal surgery are suitable for minimally invasive laparoscopic mobilization.